2013
DOI: 10.2208/jscejhe.69.i_1099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Meandering Channel Caused by a Shape of the Alternate Bars

Abstract: the largest discharge in recorded history was observed in Otofuke River, causing riverbank erosion in various parts of the basin. Damage was especially serious in the middle reaches, where part of a dike was completely washed out. The results of a survey suggested that the cause of the dike breakage was bank erosion associated with the development of a meandering channel. As the related development mechanism and predominant factors have not yet been clarified, this remains a priority for disaster prevention. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Note that, hereinafter, in order to achieve consistency with previous studies (e.g., Nagata et al, 2013), the analysis was conducted at 1 : 100 scale; however, in order to facilitate the comparison with the actual site, in this paper, the numerical values obtained in the calculation results are converted into actual measurement values.…”
Section: Watercourse Changementioning
confidence: 99%
See 1 more Smart Citation
“…Note that, hereinafter, in order to achieve consistency with previous studies (e.g., Nagata et al, 2013), the analysis was conducted at 1 : 100 scale; however, in order to facilitate the comparison with the actual site, in this paper, the numerical values obtained in the calculation results are converted into actual measurement values.…”
Section: Watercourse Changementioning
confidence: 99%
“…That is to say, there is a possibility that the development of meandering flows in the flood occurred under the interrelated influence between the mechanism of sandbar development and the mechanism of meandering channel development operating in the low-water channel. Previous studies conducted by the authors (e.g., Nagata et al, 2013) addressed sandbar topography as a factor in the development of meandering flow. Experiments and analyses confirmed that the topography of alternating bars can be a factor in the development of meandering channels.…”
Section: Introductionmentioning
confidence: 99%
“…Given the above, it was determined to be appropriate to perform the analysis at a model scale that was confirmed to be able to reproduce hydraulic and sediment transport phenomena, and then to convert the obtained results to those at actual scale and discuss the phenomena that occurred at the actual place. Note that, hereinafter, in order to achieve consistency with previous studies (e.g., Nagata et al, 2013), the analysis was conducted at 1 : 100 scale; however, in order to facilitate the comparison with the actual site, in this paper, the numerical values obtained in the calculation results are converted into actual measurement values.…”
Section: Watercourse Changementioning
confidence: 99%
“…Previous studies conducted by the authors (e.g., Nagata et al, 2013) addressed sandbar topography as a factor in the development of meandering flow. Experiments and analyses confirmed that the topography of alternating bars can be a factor in the development of meandering channels.…”
Section: Introductionmentioning
confidence: 99%